CHANGE AND POLITICISATION OF MANAGEMENT IN LITHUANIAN PUBLIC SECTOR ORGANISATIONS - Nakrošis, Vitalis (Politologija, 2014)
This introductory article presents the common research questions of this special issue and offers a joint framework for analysing the change and politicisation of the senior levels of management of different groups of Lithuanian public sector organisations (agencies, state-owned enterprises, personal health care organisations and educational organisations). A comparison of all contributions to this special issue revealed that repeating alterations of governing majorities and governments best explain the frequent turnover of heads of different Lithuanian public sector organisations (except those of personal health care and educational organisations). However, their politicisation is associated with party entrenchment in power, density of the party networks and politicians’ beliefs. The factor of civil service legislation and its enforcement is only important in the case of ministerial agencies whose heads hold career civil service positions. Furthermore, variations in the scope of politicisation are related to such administrative factors as the political salience of policy areas and organisational functions, as well as the budget size. This indicates different politicisation motivations and opportunities in the public sector. Therefore, it is the interplay of political and administrative factors that determines the change and politicisation of management in various public sector organisations. In the context of alternating ruling majorities, changing governments and positions, patronage strategies are exercised by political parties and incumbent managers on the ‘top-down’ or ‘bottom-up’ basis. These strategies are more actively pursued in policy areas and organisations that are characterised by higher political salience, larger funding or revenue. The likelihood and scope of politicisation is also affected by such facilitating factors as party networks or such constraining factors as legal regulation of the civil service. These results of politicisation research to a large extent correspond to the previous theoretical propositions based on a game theory (prisoner’s dilemma) approach. Competing party blocs exercise patronage strategies, responding to their opponents’ behaviour in office. If one party bloc politicises the positions of career managers, a competing bloc attempts to force the incumbent managers out of office through organisational restructuring and changing the status of civil service positions. Although political parties may be aware of the negative effects of politicisation, as rational actors they may have no interest in discontinuing their patronage practices in the absence of party cooperation and credible agreements concerning the professional management of public sector managers. The mechanism of ‘top-down’ politicisation can account for the level of politicisation and its dynamics at the central level, especially among the government agencies and state-owned enterprises. However, unlike at the central level, managers of local-level organisations (especially personal health care organisations, educational organisations and forestry companies) are involved in a different politicisation game. First, if under the ‘top-down’ politicisation mechanism political parties exercise patronage in order to reward loyal party members and control decision-making, under the ‘bottom-up’ politicisation mechanism some heads of public sector organisations themselves engage in patronage relations in order to keep their managerial positions, reward loyal members of their organisations and control organisational performance. Second, these mechanisms also differ in terms of politicisation results and processes: if ‘top-down’ politicisation results in high politicisation and low institutional stability (frequent organisational changes and managers’ turnover), the mix of a relatively stable institutional environment and high levels of actual politicisation can co-exist under ‘bottom-up’ politicisation.